Role of ROC1 protein in the control of cyclin D1 protein expression in skin melanomas - Nai, Gisele [UNESP]; Marques, Mariângela Esther Alencar [UNESP] (Elsevier Gmbh, Urban & Fischer Verlag, 2011)
A decrease in the level of the ROC1 protein, which is involved in cyclin D1 degradation, might explain an increase in cyclin D1 protein in the absence of gene overexpression. This study aimed to investigate the relationship between ROC1 and cyclin D1 expression in skin melanomas. A total of 62 cases of primary skin melanomas and 58 cases of compound melanocytic nevi were assessed. Immunohistochemistry was performed using cyclin D1 and ROC1 antibodies, and fluorescent in situ hybridization was used to assess the amplification of the CCND1 gene. ROC1 was expressed in > 50% of cells in 87.9% of the melanocytic nevus cases and in 45.2% of the melanoma cases (p = 0.0014). There was a significant negative correlation between ROC1 and cyclin D1 expression in all cases (p = 0.0008985). In comparison with cyclin D1, ROC1 expression was increased in 86.2% of the melanocytic nevi and in 45.2% of the melanomas (p < 0.001). Among the non-amplified melanomas, 50% expressed cyclin D1 in > 50% of the cells and expressed ROC1 in < 25%. ROC1 expression is negatively correlated with cyclin D1 expression, demonstrating its importance in the degradation of cyclin D1 melanomas. (C) 2011 Elsevier GmbH. All rights reserved.
Keywords: Melanoma; Cyclin D1; ROC1 protein; CCND1 gene; Ubiquitination